Exploring the Effect of Extensive Reading on Young English Learners’ Second Language Writing Achievement in a Vietnamese Primary School Setting - Nguyễn, Minh Châu; Baker, John R. (Universitas Negeri Makassar, 2023)
Extensive reading (ER) provides young English language learners (YELLs) many benefits, including the sustainable development of writing (e.g., the reading-writing relationship). However, this area is under- researched. To address this, this quasi-experimental study investigated the effect of ER on YELLs' second language writing achievement using an enhanced ER treatment. Pre- and post-Cambridge Primary English Test (PET) samples were collected and evaluated via the PET analytic rubric total band and subscales scores (Content, Communicative Achievement, Organization, Language). The results indicated that the EG outperformed the CG in total band score and three subscale bands (Content, Organization, Language), and the EG and CG performed comparably well in the fourth (Communicative Achievement). As prior research specific to ER’s effect on YELLs’ writing achievement in the Vietnam context is noticeably understudied, this study offers a starting point for future investigations.